Congenital abnormalities of the vertebral column in ferrets - Proks, Pavel; Stehlik, Ladislav; Paninarova, Michaela; Irova, Katarina; Hauptman, Karel; Jekl, Vladimir (Veterinary radiology & ultrasound, 2015)
Vertebral column pathologies requiring surgical intervention have been described in pet ferrets, however little information is available on the normal vertebral formula and congenital variants in this species. The purpose of this retrospective study was to describe vertebral formulas and prevalence of congenital vertebral anomalies in a sample of pet ferrets. Radiographs of 172 pet ferrets (96 males and 76 females) were included in this retrospective study. In 143 ferrets (83.14%), five different formulas of the vertebral column were recorded with normal morphology of vertebrae (rib attachment included) but with a variable number of thoracic (Th), lumbar (L), and sacral (S) vertebrae. The number of cervical (C) vertebrae was constant in all examined animals. Observed vertebral formulas were C7/Th14/L6/S3 (51.74%), C7/Th14/L6/S4 (22.10%), C7/Th14/L7/S3 (6.98%), C7/Th15/L6/S3 (1.74%), and C7/Th15/L6/S4 (0.58%). Formula C7/Th14/L6/S4 was significantly more common in males than in females (P < 0.05). Congenital spinal abnormalities were found in 29 ferrets (16.86%), mostly localized in the thoracolumbar and lumbosacral regions. The cervical region was affected in only one case. Transitional vertebrae represented the most common congenital abnormalities (26 ferrets) in the thoracolumbar (13 ferrets) and lumbosacral regions (10 ferrets) or simultaneously in both regions (three ferrets). Other vertebral anomalies included block (two ferrets) and wedge vertebra (one ferret). Spina bifida was not detected. Findings from the current study indicated that vertebral formulas may vary in ferrets and congenital abnormalities are common. This should be taken into consideration for surgical planning.
Keywords: křížová kost; bederní obratle; Retrospective Studies; transitional vertebra; sexuální faktory; Ribs; mužské pohlaví; radiograph; congenital anomaly; páteř; Thoracic Vertebrae; Sacrum; ženské pohlaví; zvířata; retrospektivní studie; fretky; Sex Factors; spine; hrudní obratle; krční obratle; Spine; Female; Cervical Vertebrae; Ferrets; žebra; Lumbar Vertebrae; Male; Mustelidae; Animals